2004
DOI: 10.1093/ndt/gfh013
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal dialysis with solutions low in glucose degradation products is associated with improved biocompatibility profile towards peritoneal mesothelial cells

Abstract: These results suggest that therapy with new pH-neutral low-GDP solutions contribute to an intraperitoneal milieu that improves mesothelial cell proliferation and viability. It may positively impact on the preservation of the peritoneal membrane integrity during long-term dialysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 18 publications
2
38
0
1
Order By: Relevance
“…Dialytic glucose exposure increased from 113646 to 126650 g/m 2 per day in the L-PDF group and from 100626 to 116628 g/m 2 per day in the B-PDF group (P=0.25 for group, P,0.001 for time, P=0.27 for interaction), whereas the number of cycles remained constant. Likewise, there were no statistically significant differences regarding total daily dwell time (7.861.7 and 7.861.3 hours at visit 0 and 7.060.7 and 8.061.1 hours at visit 10) and dwell volume (10076131 and 9936164 ml/m 2 at visit 0 and 10366166 and 10076157 ml/m 2 at visit 10 with L-PDF and B-PDF, respectively).…”
Section: Biochemistry and Dialysis Prescription During The Studymentioning
confidence: 95%
See 1 more Smart Citation
“…Dialytic glucose exposure increased from 113646 to 126650 g/m 2 per day in the L-PDF group and from 100626 to 116628 g/m 2 per day in the B-PDF group (P=0.25 for group, P,0.001 for time, P=0.27 for interaction), whereas the number of cycles remained constant. Likewise, there were no statistically significant differences regarding total daily dwell time (7.861.7 and 7.861.3 hours at visit 0 and 7.060.7 and 8.061.1 hours at visit 10) and dwell volume (10076131 and 9936164 ml/m 2 at visit 0 and 10366166 and 10076157 ml/m 2 at visit 10 with L-PDF and B-PDF, respectively).…”
Section: Biochemistry and Dialysis Prescription During The Studymentioning
confidence: 95%
“…The final fluid instilled after mixing is buffered at a neutral pH in contrast to the acidic milieu of conventional solutions. Numerous in vitro and animal studies showed superior biocompatibility of multichamber PD solutions (1)(2)(3)(4)(5). Recent randomized controlled trials suggest improved preservation of residual renal function (6,7) and ultrafiltration capacity (8) and lowering of systemic concentrations of advanced glycation end products (9,10), which contribute to accelerated vasculopathy and amyloidosis.…”
Section: Introductionmentioning
confidence: 99%
“…The term GDP represents a number of GDPs, such as acetaldehyde, formaldehyde, furaldehyde, glyoxal, methylglyoxal, and 5-hydroxymethylfuraldehyde [6]. Many publications describe an unfavorable effect of GDP on mesothelial cells of the peritoneum by impairing its proliferation and viability [3,7,8,9,10,11,12,13,14]. Furthermore, pH-neutral solutions are described as subjectively more tolerable [14].…”
Section: Discussionmentioning
confidence: 99%
“…net açık ortaya konulabilmiş değildir (1). 2010 yı-lında yapılan 1 yıllık gözlemsel prospektif ça-lışmada geleneksel ve düşük GDPli solüsyonlar kullanan hastalarda diyalizat TGF β, VEGF, IL6 oluşumu incelenmiştir (30 (34)(35)(36). Diyalizat IL6 dü-zeyleri bazal peritoneal transport durumu ve inflamatuvar faktörler ile ilişkili bulunmuştur.…”
Section: Periton Zarı üZerindeki Lokal Etkileriunclassified